ChemInform Abstract: A Novel Thiourea Type Organocatalyst Possessing a Single NH Functionality. Issue 47 (3rd November 2016) - Jovanovic, Predrag; Petkovic, Milos; Simic, Milena; Ivkovic, Branka; Savic, Vladimir
Abstract: The novel catalyst is designed by altering a typical H‐bonding pattern of thiourea derivatives and utilizing the potential of the bis(trifluoromethyl)phenyl motif to participate in the H‐bond formation.